Effect of oak (Quercus brantii) biochar on growth of two forage crops, Vicia sativa and Onobrychis sativa, in order to promote their cultivation potential - Shirko Ebrahimi Mohammadi; Hamed Joneidi Jafari; Soma Fathi; Fateme Naghizade Asl (Discover Applied Sciences)
Abstract Vicia sativa and Onobrychis sativa are two forage legume crops with nutritional values for humans and grazing animals. Biochar contributes to the plant growth through enhancing the soil fertility. This study was conducted to determine the effect of oak biochar as a waste of pruning practice in Zagros forests, Iran, on the growth and morphological attributes of the two species. Biochar was produced from oak wood under slow pyrolysis at 500 °C under anaerobic condition. Oak biochar was mixed to soils at three rates of 0, 3 and 6% and 2.518 kg of soil was filled in pots. The experiments were performed in 20 replications for 12 months as a completely randomized design. Responses of forage crops to addition of oak biochar were different, so that the addition of oak biochar increased the number of germinated seeds, plant height, mean diameter and the weight of aerial parts of O. sativa while in V. sativa, the stem diameter was increased significantly. Addition of 3 and 6% of oak biochar to O. sativa increased the number of germinated seeds by 72 and 86%, respectively and the weight of aerial parts by 41 and 84.5%, respectively. 6% of oak biochar amendment is suggested for the application.